Identification of SNPs in hMSH3/MSH6 interaction domain affecting the structure and function of MSH2 protein. (15th December 2021) - Singh, Sidhartha; Sharma, Siddharth; Baranwal, Manoj
Abstract: MutS homolog 2 (MSH2) is a mismatch repair gene that plays a critical role in DNA repair pathways, and its mutations are associated with different cancers. The present study aimed to find out the single nucleotide polymorphisms (SNPs) of MSH2 protein associated with causing structural and functional changes leading to the development of cancer with the help of computational tools. Four different tools for predicting deleterious SNPs (SIFT, PROVEAN, PANTHER, and PolyPhen), two tools each for identifying disease association (PhD‐SNP and SNP&GO) and estimating stability (I‐mutant and MUPro) were employed. Homology modeling, energy minimization, and root mean square deviation calculation were used to estimate structural variations. Twenty‐seven SNPs and five SNPs (double amino acid change) were identified based on a consensus approach that might be associated with the structural and functional change in MSH2 protein. Molecular docking reveals that six SNPs affect the interaction of MSH2 and MSH6. Twelve identified SNPs were reported to be linked with hereditary nonpolyposis, colorectal cancer, and Lynch syndrome. Further, selected SNPs need to be validated in an in vitro system for their precise association with cancer predisposition. Abstract : Graphical Abstract: MutS homolog 2 is a mismatch repair gene that plays a critical role in DNA repair pathways, and its mutations are associated with different cancers.